PENGARUH MODEL PEMBELAJARAN KOLABORATIF DENGAN BANTUAN WORDWALL TERHADAP TINGKAT PARTISIPASI PESERTA DIDIK (Studi Eksperimen Kelas V di SDN Rawamangun 02) - Anisa Rahmawati; Syarif Sumantri; Engga Dallion (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the effect of collaborative learning model assisted by Wordwall digital media on the level of participation of VA class students at SDN Rawamangun 02 Pagi. The background of the research is based on the need for learning innovations that can increase student involvement in the digital era. The research used an experimental method with pre-post-test one group control design. Data were collected through observation, teacher interviews, and questionnaires to students, and analyzed using the Wilcoxon Signed-Rank test. The results showed a significant increase in the average level of student participation, from 8.7 in the pretest to 10.6 in the posttest (maximum scale of 12). Statistical tests showed significant differences after the application of collaborative learning with Wordwall. The questionnaire results revealed that the majority of students felt helped in understanding the material, considered Wordwall interesting, easy to use, and increased enthusiasm and involvement in discussions and group work. A total of 29 out of 30 students stated that Wordwall made it easier to understand the material, and almost all students considered learning to be more interesting and fun. This finding shows that the collaborative learning model assisted by Wordwall is effective in increasing students' participation and learning motivation. This model is recommended as a reference for teachers in utilizing interactive learning media to create an active and fun learning atmosphere in the digital era.